2021
DOI: 10.3390/vaccines9030194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity in Indian Isolates of Rhipicephalus microplus Based on Bm86 Gene Sequence

Abstract: The control of cattle tick, Rhipicephalus microplus, is focused on repeated use of acaricides. However, due to growing acaricide resistance and residues problem, immunization of animals along with limited use of effective acaricides is considered a suitable option for the control of tick infestations. To date, more than fifty vaccine candidates have been identified and tested worldwide, but two vaccines were developed using the extensively studied candidate, Bm86. The main reason for limited vaccine commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The GenBank accessions of the submitted sequences were MN088493, MN095773-87, MN115793-98, MN319494-98, MN585688-706, and MT503262-82 for Bm86 ; MN047237-40 and MT642564-74 for SUB; and MT642575-89 for the TPM gene. The 578 bp nucleotide and its deduced 192 amino acid sequence of the BM86 gene of 68 field isolates revealed 95.6 to 99.8% and 93.2 to 99.5% [ 42 ] identities in the nucleotides and amino acid sequences, respectively. Phylogenetic analysis of the sequences with Indian field isolates showed two distinct clades, E and F. The F clade was formed with conserved BM86 sequences of strains from Campo Grande (Brazil), Mozambique, Thailand, and China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GenBank accessions of the submitted sequences were MN088493, MN095773-87, MN115793-98, MN319494-98, MN585688-706, and MT503262-82 for Bm86 ; MN047237-40 and MT642564-74 for SUB; and MT642575-89 for the TPM gene. The 578 bp nucleotide and its deduced 192 amino acid sequence of the BM86 gene of 68 field isolates revealed 95.6 to 99.8% and 93.2 to 99.5% [ 42 ] identities in the nucleotides and amino acid sequences, respectively. Phylogenetic analysis of the sequences with Indian field isolates showed two distinct clades, E and F. The F clade was formed with conserved BM86 sequences of strains from Campo Grande (Brazil), Mozambique, Thailand, and China.…”
Section: Resultsmentioning
confidence: 99%
“…To increase vaccine efficacy, cocktails of antigens comprising two to three antigens were attempted, and the synergistic and antagonistic effects of antigens in vaccines were also reported [ 40 ]. In contrast to cocktails of antigens, multiple antigens injected separately may elicit a better response as the chance of interference of one antigen with other can be avoided [ 41 , 42 , 43 , 44 ]. The selection of the proteins was based on the previous results using these antigens.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent years, in silico epitope prediction tools have been extensively utilised to evaluate which regions of Bm86 could be recognised by B- and T-cells and the major histocompatibility complexes (MHCs), which could potentially be candidates for peptide-based vaccines against R. microplus [ 106 , 107 ]. A 2021 study recently utilised total RNA to amplify full-length Bm86 sequences from Indian isolates of R. microplus to map the variability of the Bm86 protein in Indian strains and to predict B-cell epitopes for vaccine development [ 107 ]. This study identified nine B-cell epitopes, of which at least three epitopes showed a high degree of variability between various geographical strains of R. microplus (incl.…”
Section: Advances In Bm86 Epitope Mapping—entering the Era Of Peptide...mentioning
confidence: 99%
“…Whether the immune response elicited would confer protection against infestation in vivo remains difficult to predict, and final validation in animal vaccination and infestation studies remains paramount. Previous studies were limited to the prediction of immunogenic linear B- or T-cell epitopes for Bm86 based predominantly on murine or human MHC alleles [ 106 , 107 ]. Recently, more extensive databases and tools for investigating bovine MHCI and MHCII alleles have become available [ 139 ], allowing for more accurate in silico prediction to be conducted for bovine MHCI and MHCII epitopes.…”
Section: Advances In Bm86 Epitope Mapping—entering the Era Of Peptide...mentioning
confidence: 99%
“…In the last decades, cattle tick has represented a serious problem in Mexico and worldwide, and it has been considered a primary veterinary challenge [3]. The cattle tick has an essential economic impact in the cattle industry estimated at billions of dollars annually [4,5].…”
Section: Introductionmentioning
confidence: 99%